The Islamic Moderation Values on the Islamic Education Curriculum in Indonesia: A Content Analysis - Siswanto, Siswanto (Jurnal Pendidikan Islam, 2019)
The discourse of Islamic moderation in Indonesia is re-emerging as the phenomenon of radical religious understanding emerges. This study aims to analyze the values ​​of Islamic moderation in the curriculum of Education in Indonesia through the textbooks of Pendidikan Agama Islam and Budi Pekerti taught at the Senior High School level (SMA). The method used is content analysis. The results showed that the concept of Islamic moderation was not explicitly mentioned, but reflected in a material whose substance contained the values ​​of Islamic moderation, namely the values ​​of tolerance, democracy, simplicity, justice, and harmony. The mainstreaming of Islamic moderation values ​​in the education curriculum in Indonesia has become very important because of the emergence of concerns about strengthening extremist, intolerant and radicalism-terrorism movements in several educational institutions.